Development of an Ethnomathematics-Based LKPD on Local Cultural of Jihat Ninek Depati Intan Kemalo Sari on the Material Flat Shapes - Sari, Novita; Gunawan, Rilla Gina (Jurnal Pendidikan Matematika Universitas Lampung, 2026)
This study aims to develop an ethnomathematics-based LKPD (student worksheet) based on the local culture of Jihat Ninek Depati Intan Kemalo Sari on the material flat shapes and to determine its level of validity and practicality. The method used in this study was Research and Development with the Plomp development model, which consists of the stages of initial investigation, development, and evaluation. A limited trial was conducted with 26 ninth-grade students at State Junior High School 14 Kerinci in the 2025/2026 academic year. The instruments used in this study included a validation sheet prepared by experts and a practicality questionnaire for teachers and students. The data were analyzed using the Aiken index to measure validity and percentage analysis to assess practicality. The results of this study indicate that the developed LKPD demonstrated a high level of validity, with an average score of 0.84, and a practicality level of 81%. However, this study is limited to the validity and practicality evaluation stages and does not include effectiveness testing. This limitation is due to time constraints and the scope of the research, which focuses on product development.  Therefore, further research is recommended to examine the effectiveness of the developed LKPD in improving students’ learning outcomes and mathematical understanding through broader implementation. The findings of this study suggest that ethnomathematics-based LKPD can serve as an alternative teaching material that is relevant and meaningful, as it integrates mathematical concepts with local cultural values, while also supporting the strengthening of the Pancasila Student Profile in mathematics learning.